Controlled biopolymer roughness induced by plasma and excimer laser treatment - P. Slepicka; I. Michaljanicova; V. Svorcik (eXPRESS Polymer Letters, 2013)
A new method for biopolymer poly-L-lactic-acid (PLLA) surface nanostructuring with surface plasmon resonance appearance is proposed. The motivation of this work is to determine optimal conditions for rough or flat biopolymer surface which may find broad application in tissue engineering as biocompatible carrier for various types of cell lines. A combination of plasma pre-treatment with consequent excimer laser exposure is proposed as a method for increasing the roughness of PLLA surface and changing its morphology. The focus of this paper is to determine morphology changes in combination with mass loss changes. The ablation loss and morphology of PLLA was induced by excimer laser exposure of plasma pre-treated PLLA with different laser fluencies and number of pulses. The combination of a certain input parameters of plasma pre-treatment together with laser exposure induces extensive physico-chemical changes (morphology, contact angle, optical properties) on polymer surface with dramatic roughness increase. Gravimetric studies have revealed an extensive polymer ablation after excimer laser application. The effect of surface plasmon resonance was observed in laser modified PLLA. Conditions for PLLA surface flattening are also proposed.